Chemiresistive Sensor Arrays from Conductive 2D Metal–Organic Frameworks - Campbell, Michael G; Liu, Sophie F; Swager, Timothy M; Dincă, Mircea (Journal of the American Chemical Society, 2015)
Applications of porous metal–organic frameworks (MOFs) in electronic devices are rare, owing in large part to a lack of MOFs that display electrical conductivity. Here, we describe the use of conductive two-dimensional (2D) MOFs as a new class of materials for chemiresistive sensing of volatile organic compounds (VOCs). We demonstrate that a family of structurally analogous 2D MOFs can be used to construct a cross-reactive sensor array that allows for clear discrimination between different categories of VOCs. Experimental data show that multiple sensing mechanisms are operative with high degrees of orthogonality, establishing that the 2D MOFs used here are mechanistically unique and offer advantages relative to other known chemiresistor materials.